FLIPPED CLASSROOM LEARNING PADA PEMBELAJARAN MATEMATIKA BI-LINGUAL UNTUK MENUMBUHKAN KEMANDIRIAN BELAJAR - Wanda Nugroho Yanuarto (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2016)
Flipped classroom is a learning model that uses exciting technology that commonly used in everyday life. Therefore students are expected to learn independently and can change the negative paradigm of technology itself. The purpose of this study is to get an idea of ​​how the application of Flipped Classroom learning model in Mathematics Education students of University of Muhammadiyah Purwokerto in Mathematics Bi-Lingual subject. The results of this study are application of flipped classroom learning stages; and an overview of independent learning of students during the learning by applying flipped classroom learning model. Key words: Flipped classroom, independently of study, and learning technology